2016
DOI: 10.5812/atr.30364
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical Examination, MRI and Arthroscopy Findings in Menisco-Cruciate Injuries of the Knee: A Prospective Diagnostic Study

Abstract: Background: The aim of this study was to examine the correlation of the clinical examination, MRI and arthroscopic findings in cruciate ligaments and meniscal injuries of knee and to evaluate the accuracy of clinical examination and MRI with the gold standard arthroscopy. Methods: A prospective diagnostic double-blind study was conducted on 104 consecutive patients admitted to the outdoor/casualty with trauma to the knee complaining of knee pain/locking/ instability, from August 2012 to June 2014. All the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 25 publications
(52 reference statements)
1
18
0
Order By: Relevance
“…[11]. Previous studies showed these values ranges as for sensitivity 41-100% [2,3,11,14,15], specificity 72-100% [2,10,11,14,15], PPV 34-100% [2,14], NPV 90-100% [2,14], and accuracy 68-100% [2,3,11,14,16]. Our results of MRI for diagnosing the lateral meniscus injuries were as per the findings of the literature.…”
Section: Discussionsupporting
confidence: 86%
“…[11]. Previous studies showed these values ranges as for sensitivity 41-100% [2,3,11,14,15], specificity 72-100% [2,10,11,14,15], PPV 34-100% [2,14], NPV 90-100% [2,14], and accuracy 68-100% [2,3,11,14,16]. Our results of MRI for diagnosing the lateral meniscus injuries were as per the findings of the literature.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, a complete ACL tear was seen on MRI in 10 patients (50%) and partial tear identified also in 10 patients (50%) but in arthroscopy, a complete tear was in 14 patients (70%) and partial tear was in 6 patients (30%).This means that 4 cases with complete ACL tear was diagnosed as partial tear by MRI. Panigrahi et al (11) reported, when he studied MRI of 76 patients of ACL tear against arthroscopy, the sensitivity, specificity, PPV, NPV and accuracy were 94.7%, 78.6%, 92.3%, 84.6% and 90.4%, respectively and 4 cases with complete ACL tears were missed on MRI and detected as partial tear of ACL In our study, we have correlated the MRI finding with arthroscopy in 20 patients, we compared the finding of ACL injury in MRI with arthroscopy regarding type of injury (partial and complete), we found that sensitivity and specificity were (90%, 70%) respectively in partial ACL injury. And the sensitivity, specificity in complete ACL injury were (78.4%, 100%)respectively, which was near to the study done by Behairy et al (12) who reported that the sensitivity of MRI was 77.8% and specificity was 100 %.…”
Section: Discussionmentioning
confidence: 99%
“…To diagnose a complete anterior cruciate ligament (ACL) tear, studies show MRI to have sensitivity, specificity, accuracy and negative predictive value (NPV) of 90.9, 84.6, 88.6, and 84.6% respectively [1,2]. Furthermore, the sensitivity, specificity, accuracy, and NPV of MRI to detect medial meniscus pathology was 100, 52.6, 64 and 100%, respectively, while detection of lateral meniscus pathology was 55.6, 83.3, 75.8 and 83.3%, respectively [1,2]. MRI's objective measures of test performance are not perfect by any means, leading experts to question its overall reliability [3], while also seeking a superior method.…”
Section: Introductionmentioning
confidence: 99%